PRINCIPLES (TASKS) OF MENTAL AND ORGANIZATIONAL COMPATIBILITY AS A CONDITION OF ADAPTATION AIR LEGISLATION OF UKRAINE TO EU LEGISLATION - Yuldashev, Sergiy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The essence and guidelines to ensure the principles of (problems), mental and organizational interoperability as a condition of adaptation of Ukrainian legislation to the flying of the EU legislation. The author proves that the next steps of the management development in the aviation industry as further strengthening of the public management. Management is focused on the program and target methods.